The Otto C. Berg types at the Natural History Museum, Vienna - Escobar García, Pedro; Hille, Astrid; Lucas, Eve; Rainer, Heimo (Phytotaxa, 2015)
Over six years and before his premature death in 1866, the German botanist Otto C. Berg described more than 2100 taxa of Myrtaceae, one of the ten richest plant families on Earth. He made the most fruitful contribution to the taxonomy of this family by describing the largest part of its known biodiversity in the Neotropics. The Herbarium of the Natural History Museum of Vienna (W) holds a significant part of the Herbarium brasiliense, a seminal collection for Berg’s work, currently including the types of 25% of his names. In this contribution, we present a complete, annotated catalogue of O. Berg’s Myrtaceae names and nomenclatural types held at W with the purpose of supporting taxonomic work on the group.